Armenian Apocrypha: the short questionnaire from Adam to Moses - Stone, Michael E. (Early Judaism and its literature, 2025)
"Short Questionnaire, an Armenian question-and-answer text that survives in a seventeenth-century manuscript, draws on Armenian parabiblical traditions to systematically explore biblical events from creation to the exodus. The volume includes Michael E. Stone's translation, extensive commentary, and twenty-seven essays that trace the history of parabiblical concepts and events from the Second Temple and early Christian periods down to the second millennium. Including stories of Satan's fall from the garden, the raven's role in Abel's murder, the burial places of Adam and Eve, and Noah's fourth son, the book forms a dictionary of Armenian parabiblical traditions for scholars and students interested in reception history in early Judaism and Christianity." --Page [4] of cover